The modal logic of copy and remove - Areces, Carlos Eduardo; Ditmarsch, Hans van; Fervari, Raúl Alberto; Schwarzentruber, François (2024)
Artículo finalmente publicado en: Areces, C. E., Ditmarsch, H. van, Fervari, R. A. y Schwarzentruber, F. (2017). The modal logic of copy and remove. Information and Computation, 255 (2), 243-261. http://dx.doi.org/10.1016/j.ic.2017.01.004